Scn2a Haploinsufficiency in Mice Suppresses Hippocampal Neuronal Excitability, Excitatory Synaptic Drive, and Long-Term Potentiation, and Spatial Learning and Memory - Shin, Wangyong; Kweon, Hanseul; Kang, Ryeonghwa; Kim, Doyoun; Kim, Kyungdeok; Kang, Muwon; Kim, Seo Yeong; Hwang, Sun Nam; Kim, Jin Yong; Yang, Esther; Kim, Hyun; Kim, Eunjoon (Frontiers in Molecular Neuroscience, 2019)
Nav1.2, a voltage-gated sodium channel subunit encoded by the Scn2a gene, has been implicated in various brain disorders, including epilepsy, autism spectrum disorder, intellectual disability, and schizophrenia. Nav1.2 is known to regulate the generation of action potentials in the axon initial segment and their propagation along axonal pathways. Nav1.2 also regulates synaptic integration and plasticity by promoting back-propagation of action potentials to dendrites, but whether Nav1.2 deletion in mice affects neuronal excitability, synaptic transmission, synaptic plasticity, and/or disease-related animal behaviors remains largely unclear. Here we report that mice heterozygous for the Scn2a gene (Scn2a+/– mice) show decreased neuronal excitability and suppressed excitatory synaptic transmission in the presence of network activity in the hippocampus. In addition, Scn2a+/– mice show suppressed hippocampal long-term potentiation in association with impaired spatial learning and memory, but show largely normal locomotor activity, anxiety-like behavior, social interaction, repetitive behavior, and whole-brain excitation. These results suggest that Nav1.2 regulates hippocampal neuronal excitability, excitatory synaptic drive, long-term potentiation, and spatial learning and memory in mice.